Pemberdayaan Masyarakat melalui Komunikasi Kolaboratif dalam Program Pemerintah Daerah (Program RT Keren) di Kelurahan Bendogerit Kota Blitar - Lailin, Ulva Roifatul (Universitas Islam Balitar, 2023)
This research examines community empowerment efforts through collaborative communication in the implementation of the Government Program (RT Keren) in Bendogerit Village, Blitar City. The RT Keren program aims to increase community participation and facilitate regional development by residents and local RTs. This research uses qualitative methods through in-depth interviews, participatory observation, and document analysis to understand the impact of collaborative communication in strengthening community participation and empowerment. The research results show that effective collaborative communication encourages active citizen participation, increases understanding of the program, and stimulates community empowerment in decision making. This program has increased community participation in subdistrict activities, created a greater sense of ownership among residents, and empowered communities to take an active role in decision making and program implementation.